Sistema contable en la gestión administrativa financiera para la Compañía de Transportes Pesado Rutas de Bolívar TRANSRUBOL S.A. cantón Guaranda, provincia Bolívar, en el año 2016 - Cando Bósquez, Evelyn Pamela (2016)
This research was performed by a field study led to the Company Heavy Transport Routes Bolivar TRANSRUBOL S.A., discovering as a problem the lack of an automated accounting system making the information generated currently not timely; that accounting is projected only in order to comply with tax obligations at the end of the year; the financial planning of the company is not optimal, since the absence of timely information new sources of information why the following hypothesis arises ¿What is the impact the lack of an accounting system automated administrative financial management created the Company Transports Heavy Routes of Bolívar TRANSRUBOL SA town Guaranda, Bolívar province in 2016? which is proven by Chi-square resulting in the feasibility of implementing an automated accounting system because it is not complex and helps us get more reliable and timely information. To achieve the objective a background study using methods and research techniques such as surveys, interviews were conducted; conclusion was verified that according to the empirical records kept by the accountant led to deficits and result was the discovery that applying the proposed automated accounting system found surplus for the exercise. The accounting information will help the manager and their managers to better decision-making, to raise management long-term policies and especially to meet legal obligations such as providing financial documentation to the Superintendency of Companies to the Internal Revenue Service.